Cape Verde : Joint Staff Assessment of the Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2003)
The Poverty Reduction Strategy Paper (PRSP) will draw on the national poverty alleviation plan, the grand options plan, and the national development plan. The government has successfully implemented a macroeconomic stabilization program, formulated a plan to support private sector development, and sustained its good performance in the education sector. Progress has been realized in most of the key areas highlighted in the assessment of the interim PRSP. Executive Directors encourage the government to participate in the general data dissemination system.